PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARISINDEPENDEN, KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2014-2016) - Burhan Wijaya, 14.05.52.0033; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2018)
This research is to examine the effect of nstitutional ownership, independent commissioner, audit quality and audit committee on tax avoidance. The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange during the period 2014-2016. The sample of this research is obtained by using purposive sampling method, where only 71 companies listed in Indonesia Stock Exchange fulfill all criteria, so that obtained 213 data used as research sample to be processed. This research uses multiple linear regression model to test the influence of each variable to tax avoidance. The results of the analysis in this study indicate that institutional ownership and audit quality have no significant positive effect. While independent commissioners and audit committees have a negative effect on tax avoidance. Keywords: Tax Avoidance, Institutional Ownership, Independent Commissioners, Audit Quality and Audit Committee.